1871 Tex. Laws 25, An Act to Regulate the Keeping and Bearing of Deadly Weapons. § 1 - (:unkn) unknown (General Publisher, 1871)
Prohibited the carrying of a concealed pistol, dirk, dagger, slungshot, sword cane, spear, brass knuckles, Bowie knife, or any other kind of knife used for offense or defense, unless carried openly for self-defense. Punishable by fine of $20-100, forfeiture of the weapon, and for subsequent offenses, imprisonment up to 60 days.
--
Keywords: CARRY - CONCEALED